Predisposing Faktor Kunjungan Balita Ke Posyandu Di Desa Ketajen Gedangan Sidoarjo: Predisposing Factors for Toddler Visits to Posyandu in Ketajen Gedangan Village, Sidoarjo - Cholifah, Cholifah; Rosyidah, Rafhani; Kusumawardhani, Paramitha Amelia (Jurnal Kebidanan Midwiferia, 2017)
The target achievement of balita weighing in posyandu of Desa Ketajen Gedangan 2016 is still low (56,5%) from National target (87%). Behavior of toddler visit is influenced by predisposing factor, supporting factor and pushing factor. The purpose of this research is to see the correlation of predisposing factor with visit of toddler to posyandu in Desa Ketajen Gedangan Sidoarjo. The design of the analytic study uses primary data by distributing questionnaires and secondary data by looking at KIA / KMS books. Sample 97 of 128 population that is mother mother who come to posyandu in May 2017, taken by Proportional Random sampling. Data were included in the frequency table and cross table and then analyzed bivariate using Chi Square and Exact Fisher test with α = 0,05.The result of the research is good knowledge (86%), positive attitude (89,7%), secondary education (76,3%), unemployment status (57,7%), mother age <35 years (82,5%), Regular visits (75.3%). Result of knowledge test with P = 0,000 visit, attitude with visit of underfive P = 0,014, education with toddler visit P = 0,255, job status with visit of underfive P = 0,005 and age of mother with visit of underfive P = 0,757. Conclusion of research there is correlation of knowledge, attitude, job status with toddler visit and no relation of education, age of mother with toddler visit. Suggestion of health officer can improve mother's knowledge about toddler visit through health promotion in order to have positive attitude, so mother do toddler visit to posyandu.